HUBUNGAN KECEMASAN MAHASISWA MENGHADAPI DINAS PRAKTEK KLINIK KEPERAWATAN PADA SAAT PANDEMI COVID 19 VARIAN OMICRON - Edita Revine Siahaan (Jurnal Ilmu Keperawatan Indonesia, 2022)
In Lampung Province covid 19 data ad of january 29, 2022 with 3.826 cases of death, 49.847 confirmed cases and 45.553 cases of completed isolation. Nursing students are required to face clinical nursing practice in hospitals during the covid 19 pandemic. Excessive anxiety will have adverse effect on students such as experiencing sleep disturbances, anxiety, fear and if it cannot be controlled property it will have a negative impact on students, this is knowing. The purpose of this study was to determine the relationship between student anxiety and the clinical practice of nursing during the omicron variant of the covid 19 pandemic. The method in this research uses quantitatve research. The research design used in this research is descriptive correlation using a cross sectional approach. This research was conducted at the Bunda Delima Nursing Academy, Bandar Lampung on January 18, 2022. The result showed that there was a relationship between student anxiety facing the clinical practice of nursing during the omicron variant of the covid 19 pandemic. Keywords: Anxiety, Clinical Practice, Omicron.